The medico-legal principle of confidentiality in doctor-patient relationships in Nigeria (2018)
The bedrock of a doctor-patient relationship is confidentiality, and every person has the right to keep his/her personal information private and confidential from the public. The effect of confidentiality on patients is that it helps patients seeking medical advice to be open with their doctors and trust same that the latter would keep such information secret and will not disclose such to others. However, the duty of confidentiality is not absolute. It can be disclosed where a patient gives his/her consent; or as required by the court of law, statutes; or public interest. Hence, this paper shall define the related concepts of privacy and confidentiality; examine the statutory framework of confidentiality in Nigeria; discuss the principles of confidentiality; instances when confidentiality can be disclosed/waived; and conclude by submitting recommendations on how confidentiality in a doctor-patient relationship can be effectively maintained in Nigeria.